New York, actually - Morgan, Sarah (Romance fiction writer) (Don Mills, Ontario, Canada : HQN, 2017)
Meet Molly, New York's most famous agony aunt, who considers herself an expert at relationships--as long as they're other people's. The only love of her life is her Dalmatian Valentine. Meet Daniel, a cynical divorce lawyer, who's hardwired to think relationships are a bad idea: if you don't get involved, no one can get hurt. But then he finds himself borrowing a dog to meet the gorgeous woman he sees running in Central Park every morning. Molly and Daniel think they know everything there is to know about relationships--until they meet each other that is.
Keywords: Advice columnists -- Fiction; Bloggers -- Fiction; Dogs -- Fiction; Manhattan (New York, N.Y.) -- Fiction; Central Park (New York, N.Y.) -- Fiction; Legal fiction (Literature); Romance fiction